Fast synthesis of α-MoO3 nanorods with controlled aspect ratios and their enhanced lithium storage capabilities - Chen, Jun Song (2012)
Uniform α-MoO3 nanorods are synthesized with controlled aspect ratios through a fast hydrothermal route. The control over the aspect ratio of these as-prepared nanorods is realized by applying different reaction times of 2−20 h. Specifically, the nanorods prepared with a reaction time of 2 h are, on average, much shorter in length and slightly smaller in width compared with those obtained with a longer reaction time of 20 h. The products are thoroughly characterized by FESEM/TEM/XRD/BET techniques. The electrochemical properties of the samples are analyzed using cyclic voltammetry and charge−discharge cycling. These studies reveal that the as-prepared nanorods with a smaller aspect ratio exhibit a higher initial discharge capacity, a lower irreversible loss, and better rate behavior at different charge−discharge rates. When compared to α-MoO3 submicrometer particles prepared through direct thermal decomposition, these as-prepared nanorods show much better lihtium storage properties, demonstrating that enhanced physical and/or chemical properties can be obained from proper nanostructuring of the material.